Legal Protection For Consumers For The Circulation Of Expired Food Traded Based On Law Number 8 Of 1999 Concerning Consumer Protection (Case Study Of Cirebon District Court Number : 61/PID. B/2018/PN. CBN) - Theresia Tiurma Muljanto; Wiwik Sri Widiarty; Andrew Betlehn (SEAN Institute, 2024)
The aim of this research is to implement legal protection for consumers regarding food that has expired in accordance with the Consumer Protection Law Number 8 of 1999 as well as legal considerations regarding decision Number 61/PID.B/2018/PN.CBN. This research writing method uses normative research methods because it is based on statutory regulations and doctrine, by examining the existing legal regulations and their relationship to cases that have occurred previously.The results and conclusions from writing this research are that by distributing food that has expired, the producer concerned does not comply with the rules contained in the Consumer Protection Law so that supporting institutions such as BPOM are needed to follow up and supervise food distributed in the community so that it can controlling expired consumer products so that they do not continue to harm consumers.